Printable ReRAM devices based on the non‐stoichiometric junction CuS/Cu2−xS. Issue 22 (1st October 2016) - Congiu, M.; Albano, L.G.S.; Nunes‐Neto, O.; Graeff, C.F.O.
Abstract : Hereby a novel thin film‐based configuration of redox resistive switching memory (ReRAM) based on cheap and abundant copper sulphide (CuS) is reported. The devices working mechanism is based on the junction of two layers of CuS stacked nanocrystal with different stoichiometry (CuS and Cu2− x S). CuS thin films were deposited using a fast, easy and low‐temperature drop‐casting technique. The devices shown memresistive characteristics, with well‐defined ON and OFF resistance states, inducible by voltage pulses. A polynomial model has been proposed to characterise the devices considering both space‐charge‐limited current and ionic diffusion.